Peran Guru Kelas Terhadap Pendekatan dan Model Pembelajaran Matematika Siswa Kelas IV SDN 15 Tilamuta - N. Golo, Gebriyana; Nusi, Nur Ain; Marhaba, Windi O.; Harun, Yandri; Umar, Yulianti; Uno, Winda Anggriyani (Journal of Education and Teaching Learning, 2023)
This research aims to describe the role of class teachers in approaches and models of mathematics learning for class IV students at SDN 15 Tilamuta. This research uses a qualitative approach with the type of research being descriptive. The subjects in this research were class teachers and class IV students using the discovery learning, learning model which was carried out by providing stimulation. Problem identification statement, data collection, data processing, verification and drawing conclusion/generalization. Data collection techniques are carried out through ovservation, interview and documentation. The research results show that when teacherch use the discovery learning model, 80% of students can understand the lessons given by the teacher